1971
DOI: 10.1139/y71-138
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Adenosine 3′,5′-Monophosphate and Relaxation in the Rat Uterus In Vitro

Abstract: Theophylline, diazoxide, and papaverine in low concentrations relaxed the uterus with minimal or no elevation of cyclic AMP (cAMP) levels. In higher concentrations, theophylline relaxed the uterus and increased its cAMP levels, but imidazole reversed the increase in cAMP without causing recontraction. Imidazole and NaF caused uterine contractures but did not detectably decrease cAMP levels until several minutes after the onset of contractures. The uterine relaxations produced by theophylline and/or dibutyryl c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…It has been reported that papaverine, a potent inhibitor of PDE (2), elevates the intra cellular content of cyclic AMP in rat uterus (5,6). In our previous papers (8,12), we have shown that papaverine strongly inhibited PDE from the rat uterus and increased the in tracellular level of cyclic AMP, while Aspaminol, a synthetic antispasmodic, influenced neither the PDE activity nor the intracellular level of cyclic AMP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that papaverine, a potent inhibitor of PDE (2), elevates the intra cellular content of cyclic AMP in rat uterus (5,6). In our previous papers (8,12), we have shown that papaverine strongly inhibited PDE from the rat uterus and increased the in tracellular level of cyclic AMP, while Aspaminol, a synthetic antispasmodic, influenced neither the PDE activity nor the intracellular level of cyclic AMP.…”
Section: Discussionmentioning
confidence: 99%
“…Further, some workers (3,4,5,6,7,8) have reported that papaverine and isoprenaline increased the intracellular level of cyclic AMP in the intestinal and uterine smooth muscle.…”
mentioning
confidence: 98%
“…Recently evidence is presented that papaverine, a smooth muscle relaxant, is a potent inhibitor of phosphodiesterase in rabbit aorta, rat uterus and guinea pig ileum (2,3). More recently certain workers (4,5,6,7,8) have reported that papaverine and isoprenaline increased the intracellular level of cyclic AMP in the intestinal and uterine smooth muscle. These results indicate the possibility that the actions of beta adrenergic stimulants and papaverine are mediated through an increase of the intracellular level of cyclic AMP.…”
mentioning
confidence: 98%
“…Evidence has recently been presented that papaverine, a smooth muscle relaxant, is a potent inhibitor of phosphodiesterase in the smooth muscle (2, 3). More recently, sonic workers (4, 5,6,7,8) In this paper, a change of the intracellular level of cyclic AMP after exposure of the isolated rat uterus to a test drug is estimated and examined as to whether or not the non competitive anti-oxytocin actions of antispasmodics, papaverine and Aspaminol, and isoprenaline are concerned with the cyclic AMP level in the rat uterus.Virgin female Wistar rats weighing 150 to 200 g were ovariectomized and allowed to recover more than 5 days before beginning an experiment. After sacrificing the ovari ectomized rat by a blow on the neck, the uterine horns were removed and suspended in two similar organ baths of 10 ml.…”
mentioning
confidence: 99%
“…Evidence has recently been presented that papaverine, a smooth muscle relaxant, is a potent inhibitor of phosphodiesterase in the smooth muscle (2, 3). More recently, sonic workers (4, 5,6,7,8) In this paper, a change of the intracellular level of cyclic AMP after exposure of the isolated rat uterus to a test drug is estimated and examined as to whether or not the non competitive anti-oxytocin actions of antispasmodics, papaverine and Aspaminol, and isoprenaline are concerned with the cyclic AMP level in the rat uterus.…”
mentioning
confidence: 99%